Medicinal and Phytochemical Profiling of Artocarpus altilis - Tewari, Brij Bhushan (Chemistry and Biochemistry: Research Progress Vol. 2, 2025)
Breadfruit, Artocarpus altilis, and Fosberg have been a staple food and traditional crop in the Pacific for more than 3000 years and are widely cultivated in the Caribbean and other tropical regions. Breadfruit contains phytochemicals that have the potential as an insect repellent. Medical benefits of Breadfruit extracts include cardiovascular health, good for skin, reduced diabetes, dental health, energy booster, bone health, sleep better at night, and resistance against infection. The wood of Breadfruit is one of the most valuable timbers in the construction of traditional houses. Breadfruits contain phytochemicals that have the potential as an insect repellent. Breadfruit (Artocarpus altilis) is a good source of essential amino acids (leucine, isoleucine and valine). Artocarpus altilis commonly known as breadfruit, is one of the economically important trees, which is being used for fuel, food, folder, gum, dye for textiles, starch as adhesives, medicine etc. The aim of the present book chapter is to present phytochemical analysis, antifungal, antibacterial screening of acetone, ethanol and methanol leaves extract of Artocarpus altilis also to report current relevant literature on similar research interest. The plant material leaves of Artocarpus altilis were collected from the University of Guyana Road, Cummings Lodge, Guyana. The leaves were dried in an oven at 50-55ºC for 72 h. The moisture content is calculated. The dried leaves were ground and extracted in each acetone, ethanol and methanol solvent. Extracts were collected and evaporation of solvent was done on rotavapour. The respective solvent was added to the viscous semi-solid liquid extract to make up the desired volume of extract solution. The antimicrobial and antifungal activity of both plants were examined by well diffusion method, poison plate method, paper disc plate method and streak plate methods. In Artocarpus altilis leaf extract studies, maximum and minimum antimicrobial potential was observed for methanol and acetone solvent extracts, respectively. All plant extracts showed antimicrobial potential toward the organisms Staphylococcus aureus, Escherichia coli and Candida albicans. The maximum inhibitory zone for methanolic leaf extract of Artocarpus altilis was observed to be (125 µL: 0.4 9 mm against C. albicans); (125 µL: 0.53 mm against C. albicans); (125 µL: 0.51 mm against C. albicans); (125 µL: 0.36 mm against C. albicans) by well diffusion, poison plate, paper disc plate and streak plate methods, respectively. The phytochemical analysis of the methanol leaves extract of breadfruit tested positive for flavonoids, terpenoids, phenol, phlobatannins, steroids and Phyto steroids and negative for tannins, saponins, alkaloids and cardiac glycosides. It is concluded that Artocarpus altilis plant extract can be used as an anti-diabetic, anti-pyretic, anti-diarrheal, analgesic, anti-inflammatory, hypoglycemic, anti-fertility, insecticidal, anti-proliferative, immunomodulatory crude drugs. It is also found from this study that the inhibitory zone or antimicrobial potential of leaf extract increases as the amount increases.